Slotted labyrinthotomy approach with customized electrode for patients with common cavity deformity. (12th May 2017) - Wei, Xingmei; Li, Yongxin; Fu, Qian‐jie; Gong, Yue; Chen, Biao; Chen, Jingyuan; Shi, Ying; Su, Qiaotong; Cui, Danmo; Liu, Ting
Abstract : Objectives/Hypothesis: Cochlear implantation for patients with common cavity deformity (CCD) can be difficult, with a higher incidence of intra‐ and postoperative complications; outcomes with CCD patients are also highly variable. In this study, surgical time was compared between the traditional facial recess approach (TFRA) and the transmastoid slotted labyrinthotomy approach (TSLA). Audiological outcomes and the benefit of using customized electrode arrays for CCD patients are also discussed. Study Design: Retrospective review of 13 cochlear implant (CI) patients with CCD. Methods: Six patients were implanted with the TFRA using traditional electrodes, and seven patients were implanted with the TSLA using customized electrodes. Intra‐ and postoperative complications were reviewed. Audiological outcomes were measured 3 months to 2 years after CI activation. Results: The mean surgical time for TSLA group was nearly half as long as for the TRFA group ( P < .05). Although mean audiological outcomes were better for the TSLA group, there was no significant difference between groups ( P > .05). Conclusions: For CCD patients, TSLA for cochlear implantation is recommended due to shortened surgical time; customized electrode arrays may be additionally advantageous in terms of audiological outcomes. Level of Evidence: 4. Laryngoscope, 128:468–472, 2018